Experimental Investigation of Effects of Wing Camber on Drag for a Bio-Mimic MAV Flapping Wing / H. Yusoff ... [et al.] - Yusoff, H.; Suhaimi, S.; Hyie, K.M; Iswadi, N.; Farhan, A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Flapping-Wing Micro Air Vehicles (FW-MAVs) are small hand-held flying vehicles that can maneuver in constrained space owing to its lightweight, low aspect ratio and can fly in low Reynolds number environment. In the present study, the aerodynamic characteristics such as time-averaged lift camber wings with different five wind tunnel models having 6, 9, 12, and 15% camber were developed are compared with those of a flat wing to assess the effects of camber wing on the aerodynamic performance for flapping flight applications. The experiments were performed in an open circuit wind tunnel with of non-return airflow with a test section of (0.3m x 0.3m) and capable of speeds from 0.5 to 30 m/s. The time-averaged lift as functions of advance ratio of the flapping motions with respect to the incoming flows are measured by using a strain gauge balance and KYOWA PCD-300A sensor interface data acquisition system. It is found that camber would bring significant aerodynamic benefits when the flapping flight is in unsteady state regime, with advance ratio less than 1.0. The aerodynamic benefits of camber are found to decay exponentially with the increasing advance ratio. Cambered wing show significantly higher lift in comparison with the flat wing.